Coming Home - Emily Cashwell (Grounded Theory Review: An International Journal)
The theory of coming home is a three-stage classic grounded theory that details an individual’s initial exploration of the world in childhood, followed by the subsequent abandoning of their authentic self and then the life-long journey back home to their most authentic being. In the first stage of the process, individuals act and express in authentic ways and receive feedback from the environment about which aspects of themselves are acceptable and which are not. In the second stage of the process, driven by feelings of shame and lowered self-worth or the awareness that certain aspects of themselves are unacceptable, individuals engage in abandoning behaviors to fit in and avoid rejection. After months, years, or even decades of increasing awareness about these behaviors, individuals may enter the third stage of the process, during which they come to re-explore, accept, and embrace their authentic selves.